Trends and risk factors of lung cancer in China - He, Siyi (Chin J Cancer Res, 2020)
China is faced with heavy burdens caused by lung cancer, which has climbed to the top of both cancer incidence and mortality spectrums. The age-standardized rates of incidence and mortality have shown a trend of gradual up-trends in the last decades, while the crude rates rise much quickly due to the aging of population. Although the improvement in health care has contributed to better survival of lung cancer, its prognosis is still challenging. Apart from the common risk factors such as tobacco use, air pollution, and occupational hazards, some specific factors like Chinese-style cooking also have posed great threats to human health. In light of such national conditions, specific interventions should be conducted to curb the burden of lung cancer including smoking cessation, improvement of air quality, early detection and effective treatment of lung cancer.